2017
DOI: 10.1155/2017/2962316
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective and Cognitive‐Enhancing Effects of Microencapsulation of Mulberry Fruit Extract in Animal Model of Menopausal Women with Metabolic Syndrome

Abstract: Currently, the neuroprotectant and memory-enhancing agent for menopausal women with metabolic syndrome is required. Based on the advantages of polyphenolics on numerous changes observed in menopause with metabolic syndrome and the encapsulation method, we hypothesized that microencapsulated mulberry fruit extract (MME) could protect brain damage and improve memory impairment in an animal model of menopause with metabolic syndrome. To test this hypothesis, MME at doses of 10, 50, and 250 mg/kg was given to fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…The cognitive enhancing effect of PMG observed in this study corresponded with the previous study which showed the cognitive enhancing effect following cerebral ischemia [ 9 , 11 ]. Currently, it has been demonstrated that memory function is associated with the changes in the cholinergic system, ERK signal transduction, and brain structural changes in the hippocampus [ 6 , 7 ]. A recent study has revealed that not only the hippocampus but also the prefrontal cortex plays crucial roles in spatial memory [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The cognitive enhancing effect of PMG observed in this study corresponded with the previous study which showed the cognitive enhancing effect following cerebral ischemia [ 9 , 11 ]. Currently, it has been demonstrated that memory function is associated with the changes in the cholinergic system, ERK signal transduction, and brain structural changes in the hippocampus [ 6 , 7 ]. A recent study has revealed that not only the hippocampus but also the prefrontal cortex plays crucial roles in spatial memory [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome (MetS), a complex disorder consisting of hyperglycemia, hypertension, hypertriglyceridemia, low high-density lipoprotein cholesterol (HDL-C) levels, and central obesity [ 1 ], increases the risks of both memory impairment [ 2 ] and brain dysfunction such as stroke [ 3 ]. It has been shown that MetS raises the risk of dementia [ 4 6 ]. The underlying mechanism of memory impairment in MetS appears to be associated with the reduction of many factors including the function of the cholinergic system and signal transduction via the ERK pathway together with the reduction of neuron density in the hippocampus [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mulberries contain bioactive components, such as alkaloids and flavonoids [23][24][25] and when dried possess antioxidant, antimicrobial, antidiabetic, antiobesity, and anti-inflammatory properties [26][27][28][29][30][31][32][33][34]. Qualitative analysis by the HPLC-DAD-ESI-MS/MS method has previously been used to identify six nonanthocyanin phenolics from two mulberry varieties: 4-caffeoylquinic acid, chlorogenic acid, protocatechuic acid, quercetin, rutin, and taxifolin.…”
Section: Isolation and Identification Of Flavonoid Compounds In Mulbementioning
confidence: 99%